2014
DOI: 10.1177/1035719x1401400203
|View full text |Cite
|
Sign up to set email alerts
|

Combining Realism with Rigour: An Evaluation of a National Kitchen Garden Program in Australian Primary Schools

Abstract: School garden and kitchen-based activities have potential as health-promoting school initiatives but lack well-designed evaluation frameworks. This article outlines an evaluation of a national kitchen garden program conducted in Australian primary schools. The aim was to evaluate the implementation and impact of a national garden and kitchen program in Australia, including child and health-related impacts of the program, and program implementation factors. The evaluation was undertaken using a multi-component,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Running in 10 per cent of schools, the program supports students to grow, prepare, cook, and eat plant-based foods. It has been demonstrated to encourage children to eat more vegetables and reconsider the need for meat to complete a meal (Yeatman et al, 2012).…”
Section: Ideasmentioning
confidence: 99%
“…Running in 10 per cent of schools, the program supports students to grow, prepare, cook, and eat plant-based foods. It has been demonstrated to encourage children to eat more vegetables and reconsider the need for meat to complete a meal (Yeatman et al, 2012).…”
Section: Ideasmentioning
confidence: 99%
“…Davis et al (2015) discuss reviewing 13 studies looking at the impact of garden-based programmes during and after school. An evaluation of Stephanie Alexandra Kitchen Garden Scheme confirmed that the initiative resulted in improved nutritional knowledge and nutritional benefits for learners (Block, Johnson, & SAKG, 2009; Yeatman et al, 2013). The popular success of these programmes has attracted widespread media attention and thus SBGs are remaining a familiar aspect of Australian school culture (Cutter-Mackenzie, 2009; Malone & Tranter, 2005).…”
Section: Benefits Of Sbgsmentioning
confidence: 99%
“…The potential of network effects is particularly large where community ownership of health promotion extends to integrating strategies into practice and policies of community institutions. For example, integration of the Stephanie Alexander Kitchen Garden Program kitchen and garden lessons into school curricula Yeatman et al 2014) or the potential for policy integration of early childhood movement guidelines into early childhood care settings (Okely et al 2017).…”
Section: Introductionmentioning
confidence: 99%